3.4% Solar‐to‐Ammonia Efficiency from Nitrate Using Fe Single Atomic Catalyst Supported on MoS2 Nanosheets. (22nd December 2021) - Li, Ji; Zhang, Yuan; Liu, Chao; Zheng, Lirong; Petit, Eddy; Qi, Kun; Zhang, Yang; Wu, Huali; Wang, Wensen; Tiberj, Antoine; Wang, Xuechuan; Chhowalla, Manish; et al.
Abstract: Electrochemical synthesis of NH3 is a carbon‐free alternative to the traditional Haber–Bosch process. Obtaining NH3 from environmental pollutants, such as nitrates or nitrites, is a more practical route than from the nitrogen reduction reaction (NRR) due to the difficult cleavage of the inert triple bond of nitrogen gas. Here, a novel heterogeneous catalyst is reported based on iron (Fe) single‐atoms supported on 2D MoS2 (Fe‐MoS2 ) for the nitrate reduction reaction (NO3 RR). Fe‐MoS2 exhibits remarkable performance with a maximum Faradaic efficiency of 98% for NO3 RR to NH3 at an onset potential of − 0.48 V versus the reversible hydrogen electrode (RHE) as confirmed by the isotopic nuclear magnetic resonance (NMR) analyses. Density functional theory (DFT) calculations reveal that the enhanced selectivity for the production of NH3 from single Fe atoms supported on MoS2 is attributed to a reduced energy barrier of 0.38 eV associated with de‐oxidation of *NO to *N. The catalysts are coupled to an InGaP/GaAs/Ge triple‐junction solar cell to demonstrate a solar‐to‐ammonia (STA) conversion efficiency of 3.4% and a yield rate of 510 µ g h −1 cm −2 . The results open new avenues for the design of single‐atom catalysts (SAC) for the realization of solar‐driven ammonia production. Abstract : Inspired by the active sites of natural enzymes, a catalyst is designed for the nitrate reduction reaction based on iron single atoms supported on 2D MoS2 nanosheets. Near‐unity selectivity is demonstrated for the formation of NH3 with a solar‐to‐ammonia efficiency of 3.4% when coupled to an external InGaP/GaAs/Ge triple‐junction solar cell.